Corrective Bracing for Severe Idiopathic Scoliosis in Adolescence: Influence of Brace on Trunk Morphology - Edyta Kinel; Tomasz Kotwicki; Wanda Stryła; Andrzej Szulc (The Scientific World Journal)
Aim. The aim of the work was to study whether wearing a corrective brace by adolescent girls with severe idiopathic scoliosis can influence external shape of the trunk. Methods. Comparison of clinical deformity of two groups of girls matched for age and Cobb angle: group (1) of 23 girls, aged 14.9±1.3 years, Cobb angle 55.0°±6.8°, who refused surgical treatment and have been wearing Chêneau brace for more than 6 months, compared with group (2) of 22 girls, aged 14.1±1.8 years, Cobb angle 59.7°±14.6° never treated with corrective bracing. Clinical deformity was assessed with the Bunnell scoliometer (angle of trunk rotation ATR) and surface topography (posterior trunk symmetry index POTSI and Hump Sum HS). Results. The ATR in the primary curvature was 11.9°±3.4° (5°–18°) in group 1 versus 15.1°±5.6° (6°–25°) in group 2 (P=0.027). The HS was 16.8°±3.8 versus 19.2°±4.6, respectively, P=0.07. The POTSI value did not differ between groups. Conclusion. Girls with Cobb angle above 45 degrees, who have been subjected to brace treatment, revealed smaller clinical deformity of their back comparing to nontreated girls having similar radiological curvatures.